2016
DOI: 10.3892/etm.2016.3275
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Xuebijing injection against acute lung injury induced by left ventricular ischemia/reperfusion in rabbits

Abstract: Xuebijing (XBJ) is a Chinese herbal preparation. Previous studies have demonstrated that XBJ injection is able to inhibit the uncontrolled release of endogenous inflammatory mediators, attenuate inflammation, and alleviate organ damage. However, there are no relevant reports on the protective effect of XBJ against left ventricular ischemia/reperfusion (I/R)-induced acute lung injury (ALI). Therefore, the aim of the present study was to evaluate the protective effect of XBJ on ALI induced by left ventricular I/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In addition, a meta-analysis revealed that the combined treatment of XBJI and western medicine showed better efficiency than western medicine treatment alone with significantly decreasing 28-day mortality and shorting ICU stay time [ 433 ]. Pharmacological research revealed that XBJI could prevent CLP-, dichlorvos-, paraquat- or I/R-induced ALI through decreasing inflammatory responses and oxidative stress; during the process, p38 MAPK and TLR4-mediated NF-κB signaling pathways were involved [ [434] , [435] , [436] , [437] ].…”
Section: Potential Clinical Use Of Natural Compounds For Alimentioning
confidence: 99%
“…In addition, a meta-analysis revealed that the combined treatment of XBJI and western medicine showed better efficiency than western medicine treatment alone with significantly decreasing 28-day mortality and shorting ICU stay time [ 433 ]. Pharmacological research revealed that XBJI could prevent CLP-, dichlorvos-, paraquat- or I/R-induced ALI through decreasing inflammatory responses and oxidative stress; during the process, p38 MAPK and TLR4-mediated NF-κB signaling pathways were involved [ [434] , [435] , [436] , [437] ].…”
Section: Potential Clinical Use Of Natural Compounds For Alimentioning
confidence: 99%
“…It was also reported that Xuebijing injection could downregulate the expression of IL-6, IL-1, TLR4, MAPK, and NF- κ B, maintain the balance of Tregs and Th17 cells in acute lung injury 190 , 191 , 192 , 193 . Besides, Xuebijing injection processed the potential to alleviate liver damage, acute lung injury-induced left ventricular ischemia/reperfusion, sepsis-induced acute kidney injury, and sepsis-induced myocardial injury via inhibiting inflammation, apoptosis, and endothelial injury 194 , 195 , 196 , 197 , 198 , 199 . Systems pharmacological analysis revealed that Qingfei Paidu decoction could protect multi-organ including nervous system, sensory system, digestive system, and circulatory system by regulating key enzymes, G protein-coupled receptors, ion channels, and transporters 96 .…”
Section: Potential Mechanisms Of Tcm For Covid-19mentioning
confidence: 99%
“…Furthermore, XBJ has a protective effect on ALI induced by left ventricular ischemia/reperfusion (I/R) in rabbits. This may be through regulation of the inflammatory mediator TNF-α and intercellular adhesion molecule 1 (ICAM-1) expression ( Ji et al, 2016 ). According to a meta-analysis that enrolled 16 randomized controlled trials, XBJ may improve the 28-day mortality rate and symptoms in critically ill patients without severe adverse effects ( Li et al, 2018 ).…”
Section: Conventional Drugs For the Treatment Of Ardsmentioning
confidence: 99%